1998
DOI: 10.1136/vr.142.21.564
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillar biopsy and PrPSc detection in the preclinical diagnosis of scrapie

Abstract: Preliminary findings have indicated that in naturally infected sheep, fully susceptible to scrapie (vRQ-homozygous), PrPSc can be detected in the tonsils approximately one year before the expected onset of clinical disease, whereas no immunostaining can be detected in animals with a semi-resistant genotype. This paper describes the technique for taking tonsillar biopsies from sheep and gives the results of the completed experiment. In another experiment PrPsc was detected even

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(103 citation statements)
references
References 24 publications
6
93
1
3
Order By: Relevance
“…After the lag phase, PrP sc accumulates rapidly in lymphoid tissues throughout the body as well as the intestinal nervous supply, which offers the possibility of biopsy-based preclinical diagnosis. 24,25,34,35 On the other hand, preclinical dissemination of PrP sc deposits into the placenta indicates a risk of horizontal and vertical transmission by clinically healthy ewes. The finding that most cases within scrapie-affected flocks are preclinical underscores the significance of observing PrP sc accumulation in the placentas of a high percentage of infected sheep.…”
Section: Discussionmentioning
confidence: 99%
“…After the lag phase, PrP sc accumulates rapidly in lymphoid tissues throughout the body as well as the intestinal nervous supply, which offers the possibility of biopsy-based preclinical diagnosis. 24,25,34,35 On the other hand, preclinical dissemination of PrP sc deposits into the placenta indicates a risk of horizontal and vertical transmission by clinically healthy ewes. The finding that most cases within scrapie-affected flocks are preclinical underscores the significance of observing PrP sc accumulation in the placentas of a high percentage of infected sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Presymptomatic and minimally invasive diagnostic approaches are therefore crucial to enhance the chance of success of any possible interventional approach. It has been shown that PrP Sc could be detected in the tongue of a vCJD patient [82], at preclinical stages in tonsils of sheep infected with scrapie [83] and in human appendices [84], indicating that lymphoid tissue biopsies could in principle be used for early diagnosis of vCJD. In addition, efforts are currently made to develop tests that can detect PrP Sc in blood where its concentration is 100-1000 times lower than in the brain.…”
Section: Diagnostic Reagentsmentioning
confidence: 99%
“…Preclinical tests for scrapie in domestic sheep, using biopsy samples of lymphoid tissues from the palatine tonsil, 5 third eyelid, 4 and rectal mucosa, 2,3 have been described. Preclinical diagnostic tests for CWD have been described for mule deer using biopsy tissues of palatine tonsil 10 and rectal mucosa.…”
mentioning
confidence: 99%